Peningkatan Pengetahuan dan Kesadaran Ibu Rumah Tangga Sebagai Manager Rumah Tangga Untuk Pencegahan Stunting melalui Penerapan Program KASEP di Puskesmas Marga Jaya - Mertien Sa'pang; Harna Harna; Prita Dhyani Swamilaksita; Maria Tambunan; Syukriah Usman (I-Com: Indonesian Community Journal, 2024)
Currently, overcoming and preventing stunting is one of the main objectives of health programs in the Margajaya Health Center. Therefore, strategies are needed to overcome the determining factors both at the individual and household levels. One of them is through providing continuous nutrition education with material that is simplified so it is easy to understand. The service team has developed the KASEP (Komunikasi Antarpersonal dan aplikasi messenger Peduli stunting) program which aims to increase participants' capacity to prevent stunting. This program provides knowledge about balanced nutrition applications through an interpersonal communication approach, as well as the latest information on chatbot-based messenger applications (WAR). Based on the results of the pre-test and post-test, participants showed a significant increase in knowledge. In addition, most participants felt that through WhatsApp autoreply they obtained the information they needed, and the chatbot format such as discussing with friends made it easier for them to adapt.